CAN RELIGION GIVE SCIENCE A HEART? - Kozhamthadam, Job (Journal of Dharma, 1993)
We live in an age that has witnessed many marvels in the field of science and technology. Almost every day new items are being added to the already impressive treasury of scientific discoveries. They have transformed our way of life through and through. lntercontinental travel has become an everyday affair; many are already mooting of inter-planetary voyages. Less and less fall victims to fatal diseases, more and more live longer. Open-heart surgery and such hitherto unimaginable surgical •operations are becoming almost standard treatment, letting patients new leases of life. Indeed, the transformation has been all-permeating.